Efficient Attendance Management System Based on Facial Recognition - Choudhary, Setu; Kakaji, Aayush; Pranay, Kusuma; Prabhu, P (International Journal of Engineering and Technology, 2018)
A Face recognition system is an application of computer vision which is capable of performing two major tasks identifying and verifying a person fromÂ  given data base. The objective of this paper is to design an effective attendance system which is based on facial recognition and intend to reduce the manual efforts of the teacher. In the conventional attendance system there are several issue like fake attendance, time consumption, manipulation of attendance. The algorithm used is named fisher face algorithm, which is already in use but it gives an accuracy of 5-6% and the amount of faces it can detect is comparatively less, Here we intend to use fisher face algorithm with the help of support vector machine(SVM). The system is trained with database faces.Â  The data gets updated in the portal which is accessed by the faculty and the students. This paper is a speculative model of attendance management system using facial recognition.